PERANAN INTEGRASI NILAI-NILAI ISLAM DALAM PEMBELAJARAN MATEMATIKA - Imamuddin, M.; Isnaniah, Isnaniah (Kaunia: Integration and Interconnection Islam and Science Journal, 2023)
The religious attitude of students is an attitude that must be developed in learning activities. For this reason, teachers must be able to carry out quality learning in every learning activity, including in learning mathematics. Students' religious attitudes can be developed in learning mathematics by integrating Islamic values ​​in the process. This study aims to map the role of integration of Islamic values ​​in learning mathematics. This study uses SLR (Systematic Literature Review) research, where the data source is obtained from articles that have been published by OJS (Online Journal System). Articles obtained through Google search are grouped and tabulated based on the similarity of results/conclusions in the results of the articles. After being tabulated, further analysis is carried out and at the end it is reduced and makes conclusions. Based on research data, the results obtained regarding the role of integration of Islamic values ​​in learning mathematics are as follows: The integration of Islamic values ​​plays a role in increasing students' positive character, especially religious attitudes, increasing students' motivation and interest in learning mathematics, improving students' abilities in mathematics such as communication, reasoning , solving problems, connections, mathematical literacy, and being able to improve student learning outcomes. Based on these findings, it is hoped that educators, especially mathematics teachers, will always integrate Islamic values ​​in learning mathematics.